THE RELATIONSHIP BETWEEN HUSBAND'S KNOWLEDGE AND SUPPORT WITH PREGNANT WOMEN'S VISITS DURING THE COVID-19 PANDEMIC - Marlin W.M.Liem; Afnani Toyibah; Lisa Purbawaning Wulandari (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
The Visits of pregnant women are one of the important indicators for pregnant women during pregnancy. Regular ANC visits can detect early complications during pregnancy, so they can be treated early. Husband's knowledge and husband’s support for regular ANC visits, even during the Covid-19 pandemic, is very important to encourage pregnant women to regularly attend ANC visits. The purpose of this study was to determine the relationship between husband's knowledge and support and visits by pregnant women during the Covid-19 pandemic. The design used is an analytical survey with a cross sectional approach. A sample of 30 respondents with total sampling technique. The research instrument was the husband's knowledge and support questionnaire for the regularity of ANC visits by looking at the mother's MCH handbook. The research results obtained that knowledge is included in the good category, namely as many as 12 respondents (40%). Husband support, half of respondent which did not support, namely as many as 16 respondents (53.3%). Part of the regularity of visiting pregnant women is irregular, namely 17 respondents (56.7%). The results of data analysis using Spearman correlation rho value of r 0.020 with significance (p value) = 0.05. Conclusion: there is a significant relationship between knowledge and regularity of visiting pregnant women during the Covid 19 pandemic. It is hoped that husbands need to increase their knowledge and support to motivate pregnant women to visit ANC even during the Covid-19 pandemic